Answers

The Brainliest Answer!
2016-03-17T17:14:55+05:30
In PQR and QPS,
<P=<Q(prop. of isotrap.)
PQ=PQ(common)
PS=QR(given)
Therefore, PQR is congruent to QPS.
PR=QS(C.P.C.T)
.................................................
pls mark as brainliest answer.(pls pls!!)

1 5 1
  • Brainly User
2016-03-17T18:53:42+05:30

in triangle qps and triangle pqr

ps = qr (given)

pq = pq (given)

<spq = <rqp (property of iso. trapezium)

therefore, triangle qps = triangle pqr (by S.A.S. axiom)

also, pr = qs (by C.P.C.T.)

----------------Hence, Proved.----------------------------


0
Hoping to be marked as Brainliest answer;)